PEMANFAATAN MEDIA PEMBELAJARAN GOOGLE SITES DALAM UPAYA MENINGKATKAN PERHATIAN BELAJAR BAHASA INDONESIA MATERI MENULIS BERITA SISWA KELAS VIII SMP NEGERI 1 CURAHDAMI BONDOWOSO: SMP NEGERI 1 CURAHDAMI BONDOWOSO - OEPIK ANDRIYANI (Dewan Pendidikan Bondowoso, 2022)
The success of student learning in completing studies at the educational level that has occurred so far has not been as expected by all parties. Especially Indonesian subjects are important especially for low grade students. Therefore, as educators and teachers, teachers must be able to realize the expectations of education and schools. In essence the teaching and learning process is a communication process that must be created or realized through the activity of delivering and exchanging messages or information by each teacher and student. Messages or information can be in the form of knowledge, expertise, skills, ideas, experiences, and so on. In the teaching and learning process, the media used to facilitate teaching and learning communication is called Learning Media. Online Indonesian Learning Media Based on Google Sites as a learning medium is a medium inspired by websites and blogs. The subjects in this study were class VIII students of SMPN 1 Curahdami for the 2021/2022 academic year. This research was conducted in class VIII of SMP Negeri 1 Curahdami in 2 cycles in October 2021-November 2021. The conclusion from this study is that using Google Sites media, teacher strategies and various methods can make students active, creative and fun.